Training wearing thermal clothing and training in hot ambient conditions are equally effective methods of heat acclimation - Lundby, C.; Svendsen, I. S.; Urianstad, T.; Hansen, J.; Rønnestad, B. R. (Journal of Science and Medicine in Sport, 2021)
The objective was to compare the efficacy of three different heat acclimation protocols to improve exercise performance in the heat. Thirty four cyclists completed one of three 10-day interventions 1) 50-min cycling per day in 35 °C, 2) 50-min cycling per day wearing thermal clothing, and 3) 50-min cycling wearing thermal clothing plus 25 min hot water immersion per day. Pre- and post-intervention hemoglobin mass, intravascular volumes and core temperature were determined at rest. Heart rate, sweat rate, blood lactate concentration and core temperature were evaluated during 15-min submaximal and 30-min all-out cycling performance conducted in 35.2 ± 0.1 °C and 61 ± 1% relative humidity. There were no significant between-group differences in any of the determined variables. None of the interventions statistically altered any of the parameters investigated as part of the 15-min submaximal trial. However, following the intervention period, heat chamber, thermal clothing and thermal clothing + hot water immersion all improved 30-min all-out average power in the heat (9.5 ± 3.8%, 9.5 ± 3.6 and 9.9 ± 5.2%, respectively, p < 0.001, F = 192.3). At termination of the 30-min all-out test, the increase in blood lactate concentration, rate of perceived exertion and sweat rate were not different between the three interventions. In conclusion, daily training sessions conducted either in ambient 35 °C, while wearing thermal clothing in temperate conditions or while wearing thermal clothing combined with hot water immersion are equally effective for improving exercise performance in the heat.